A novel CUL4B gene variant activating Wnt4/β-catenin signal pathway to karyotype 46, XY female with disorders of sex development - Chunlin Wang; Hong Chen; Qingqing Chen; Yangbin Qu; Ke Yuan; Li Liang; Qingfeng Yan (Biological Research)
Abstract Background Karyotype 46, XY female disorders of sex development (46, XY female DSD) are congenital conditions due to irregular gonadal development or androgen synthesis or function issues. Genes significantly influence DSD; however, the underlying mechanisms remain unclear. This study identified a Chinese family with 46, XY female DSD due to the CUL4B gene. Methods The proband medical history and pedigree were investigated. Whole-exome sequencing was performed to analyze different variations. Transiently transfected testicular teratoma (NT2/D1), KGN ovarian cells with either mutant or wild-type CUL4B gene, and knock-in Cul4b mouse models were confirmed. The expression levels of sex-related genes were analyzed. Results A 9.5-year-old girl was diagnosed with 46, XY DSD. A hemizygous variant c.838 T > A of the CUL4B gene was detected. The mRNA and protein levels of WNT4 and FOXL2 genes were higher than those in the wild-type group; however, CTNNB1, SOX9, and DMRT1 were lower in the wild-type group in NT2/D1 cells. In KGN ovarian cells of the mutant group, the mRNA and protein levels for WNT4 and CTNNB1 were elevated. Damaged testicular vasculature and underdeveloped seminal vesicles were observed in Cul4b L337M mice. Conclusions A missense CUL4B variant c.838 T > A associated with 46, XY female DSD was identified, and may activate the Wnt4/β-catenin pathway. Our findings provide novel insights into the molecular mechanisms of 46, XY female DSD.